A comparison of Eurocodes and BS codes in the design of vertically loaded pile (b) : pile founded in clay - Koh, Yi Hong. (2013)
Pile design using British standards (BS8004:1986) will soon be replaced by Eurocode 7 (EC7). As such, practicing engineers will be expected to familiarize with the philosophy behind Eurocode 7 (EC7) so as to produce an equally competent design.